Experimental investigations on multitudinal sliding mode controller‐based interleaved shunt APF to mitigate shoot‐through and PQ problems under distorted supply voltage conditions. (18th September 2018) - Gali, Vijayakumar; Gupta, Nitin; Gupta, R.A.
Summary: This paper presents design and hardware implementation of single‐phase interleaved inverter as shunt active power filter (SAPF) to mitigate shoot‐through phenomena and power quality problems like current harmonics and reactive power compensation. Shoot‐through phenomena are 1 of the failure mode in conventional voltage source inverter (VSI) which may damage power switches. This also introduces ringing effect and temperature rise and affects the reliability and efficiency of the system. However, external dead band circuits are used to eliminate these problems, but they reduce the harmonic compensation level. Further, the multitudinal sliding mode controller (MSMC) is proposed for stabilizing the DC‐link voltage under steady‐state and transient condition of the load. This has shown an excellent tracking capability with reduced DC‐link voltage ripples compared to the conventional sliding mode and PI controllers. DC‐link energy balance theorem is used for reference current generation. The proposed topology has been modeled using MATLAB ® /Simulink environment and tested under the steady and transient condition of the load in different supply voltage conditions. A laboratory prototype has been designed and developed using dSPACE 1104 controller to validate the simulation results. The test results show the viability of the control algorithm and performance of the proposed interleaved inverter in the power quality applications.